Readmission for Acute Decompensated Heart Failure among Patients Successfully Treated with Transcatheter Aortic Valve Replacement: A PARTNER-1 Substudy. Issue 4 (4th July 2018) - Petersen, John L.; Blackstone, Eugene H.; Rajeswaran, Jeevanantham; Cohen, David J.; Douglas, Pamela S.; Hahn, Rebecca T.; Kodali, Susheel; Svensson, Lars G.; Leon, Martin B.
ABSTRACT: Background : Readmission for acute decompensated heart failure (ADHF) following transcatheter aortic valve replacement (TAVR) is common and linked with mortality. However, time course of ADHF readmissions, their risk factors, and their association with long-term outcomes are not well understood. Our objectives were to identify the temporal pattern of readmission for ADHF following TAVR, which patients are at high risk, and the association of readmission for ADHF and subsequent mortality. Methods : We evaluated 2467 patients successfully treated and discharged in the PARTNER-1 trial, and followed for 5 years. Baseline and discharge clinical, pharmacologic, procedure, and echocardiographic characteristics were considered. The likelihood and temporal pattern of ADHF readmission after accounting for the competing risk of death were assessed using nested competing-risk methodology for repeating time-related events. Risk factors were identified by unsupervised bootstrap-aggregation machine learning. Results : Admission for ADHF following TAVR was associated with an increased risk of subsequent readmission. Accounting for baseline, procedure, and discharge characteristics, we identified greater severity of post-procedure mitral and aortic regurgitation, both lower- and higher-gradient aortic stenosis, oxygen-dependent COPD, baseline calcium channel blocker and long-acting nitrate use, and longer index hospitalization length of stay as risk factors for readmission for ADHF. Conclusion : Early readmission for ADHF following TAVR was associated with clinical, pharmacologic, and echocardiographic characteristics. The resulting models may be used to identify patients at high risk for early readmission following TAVR and to suggest future prospective trials, particularly to treat combined mitral regurgitation associated with aortic stenosis.